The Role of Home Reading in the Context of a New Communicative Paradigm of Language Education - G.S. Mustayeva; M.V. Isambayeva (Genius Journals, 2023)
Our article deals with the question of revising methodological approaches for foreign language teaching. In our opinion, the transition to a competence-oriented model was determined by a shift in emphasis from knowledge of rules and norms to the effectiveness of language behavior. Homeschooling as part of the basic foreign language speaking practice allows us to implement the principles of a communicative-active approach and to solve several other problems associated with preparation for a bachelor’s degree in the field of pedagogical education
Keywords: competence; foreign language